2019
DOI: 10.1021/acs.energyfuels.8b04464
|View full text |Cite
|
Sign up to set email alerts
|

A Study for Using CO2 To Enhance Natural Gas Recovery from Tight Reservoirs

Abstract: A comprehensive study is presented on the interfacial behavior of all participating phases in a scenario of using carbon dioxide (CO2) to enhance the recovery of natural gas in tight sandstone reservoirs. Natural gas condensate is contacted with CO2 at an increasing pressure to determine the minimum miscibility pressure (MMP) by the vanishing interfacial tension method. Close to the MMP at a higher temperature, some compounds of the mixture are extracted, leaving a heavy oil fraction that remains immiscible. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
1
23
2
Order By: Relevance
“…At low to moderate pressures, the IFT course is dominated by the interaction of CO 2 with the light compounds of the crude oil, this is indicated by a steep slope that is qualitatively similar to that observed for a gas condensate/ CO 2 system as reported in (Wang et al 2019), where complete miscibility is reached at moderate pressures below 15 MPa. This can be attributed to the reduction in the intermolecular distance between CO 2 and the oil as pressure increases, thereby increasing the intermolecular forces between them (Yang et al 2015).…”
Section: Oil-co 2 Interfacial Tensionsupporting
confidence: 75%
“…At low to moderate pressures, the IFT course is dominated by the interaction of CO 2 with the light compounds of the crude oil, this is indicated by a steep slope that is qualitatively similar to that observed for a gas condensate/ CO 2 system as reported in (Wang et al 2019), where complete miscibility is reached at moderate pressures below 15 MPa. This can be attributed to the reduction in the intermolecular distance between CO 2 and the oil as pressure increases, thereby increasing the intermolecular forces between them (Yang et al 2015).…”
Section: Oil-co 2 Interfacial Tensionsupporting
confidence: 75%
“…The authors reported that higher nanoparticles concentrations required higher pressure for optimum formation erosion and better penetration. Wang et al [ 18 ] discussed the use of Sc‐CO 2 to determine the minimum miscibility pressure (MMP) using the vanishing IFT method. The authors investigated the impact of pressure and time on Sc‐CO 2 the extraction properties and effectiveness.…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…[ 16,17 ] Therefore, many studies have investigated the use of Sc‐CO 2 for enhanced oil and gas recovery from unconventional resources. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of underground stored natural gas would be more environmentally friendly during enhanced recovery processes [17][18][19][20][21][22][23], as it does not need to transfer gas from petrochemical industries [24][25][26]. Moreover, it is more economical, as it has removed unprecedented expenses to capture carbon dioxide [27][28][29][30][31][32][33][34]. Recently, due to the high productions of hydrocarbon, most of the conventional reservoirs are almost depleted, or it is not economical to produce the remained hydrocarbon [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%